2005
DOI: 10.1016/j.femsle.2005.08.034
|View full text |Cite
|
Sign up to set email alerts
|

Trichodermabiodiversity in China: Evidence for a North to South distribution of species in East Asia

Abstract: Towards assessing the biodiversity and biogeography of Trichoderma, we have analyzed the occurrence of Trichoderma species in soil and litter from four areas in China: North (Hebei province), South-East (Zhejiang province), West (Himalayan, Tibet) and South-West (Yunnan province). One hundred and thirty five isolates were grouped according to tentative morphological identification. A representative 64 isolates were verified at the species level by the oligonucleotide barcode program TrichO Key v.1.0 and the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 35 publications
7
45
0
5
Order By: Relevance
“…While these studies revealed the worldwide predominance of some species such as T. harzianum, they also revealed a putative geographic bias for a number of other taxa. This is best exemplified in a summary of the geographic occurrence of species from section Longibrachiatum (Table 1), of which, only T. longibrachiatum, H. orientalis, and T. ghanense appear to Turner et al(1997), Kullnig et al(2000), Kubicek et al(2003), Druzhinina et al(2005), Zhang et al(2005), and unpublished work in our own laboratory fulfil the criterion of a pangaean distribution, although the latter two are more frequent in warmer and tropical areas. H. schweinitzii/T.…”
Section: Geographic Distribution Of Hypocrea/ Trichodermamentioning
confidence: 90%
See 1 more Smart Citation
“…While these studies revealed the worldwide predominance of some species such as T. harzianum, they also revealed a putative geographic bias for a number of other taxa. This is best exemplified in a summary of the geographic occurrence of species from section Longibrachiatum (Table 1), of which, only T. longibrachiatum, H. orientalis, and T. ghanense appear to Turner et al(1997), Kullnig et al(2000), Kubicek et al(2003), Druzhinina et al(2005), Zhang et al(2005), and unpublished work in our own laboratory fulfil the criterion of a pangaean distribution, although the latter two are more frequent in warmer and tropical areas. H. schweinitzii/T.…”
Section: Geographic Distribution Of Hypocrea/ Trichodermamentioning
confidence: 90%
“…The use of DNA-based species identification tools has now revised many of these claims, by showing that these species actually are composed of two or more phylogenetic species, each of which displays restricted biogeography (Koufopanou et al, 2001;Geiser et al, 1998;Burt et al, 1996;Kasuga et al, 2003). The global occurrence of Trichoderma was recently investigated in several studies (Kullnig et al, 2000;Kubicek et al, 2003;Wuczkowski et al, 2003;Gherbawy et al, 2004;Druzhinina et al, 2005;Zhang et al, 2005). While these studies revealed the worldwide predominance of some species such as T. harzianum, they also revealed a putative geographic bias for a number of other taxa.…”
Section: Geographic Distribution Of Hypocrea/ Trichodermamentioning
confidence: 99%
“…muroiana is a more serious shortcoming. Studies on the distribution of Trichoderma in different habitats (Kullnig et al 2000;Kubicek et al 2003;Wuczkowski et al 2003;Zhang et al 2005) have frequently detected strains with the ITS sequence characteristic for these three species. Unfortunately, an accurate identification of species in the Rufa Clade (Viride Clade sensu Samuels et al, in manuscript) by other means (e.g., tef1 analysis) is still hampered by the fact that species limits within this clade are under revision, and both T. viride and T. koningii appear to contain several cryptic species.…”
Section: Identification Of Species Based On the Analysis Of Dna Sequementioning
confidence: 99%
“…In addition, it has been shown that several of its taxa occur as endophytes particularly in the tropical arboreous plants, and that the strains often exhibit high antagonistic activity against pathogens of these plants [15][16][17][18]. However, the importance of Trichoderma or other endophytic fungi as a part of endogenous microbial diversity and their application in the biological control of tracheomycosis on the coffee plants has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%